Six Capitals and a Local Book: An Experiment in Articulating the Value of Bruce Pascoe's Dark Emu. Issue 1 (2nd January 2023) - van Loon, Julienne
ABSTRACT: This article presents and discusses an experiment with Bruce Pascoe's Dark Emu as an inaugural case study of how we might apply the International Integrated Reporting () Framework to an Australian book title. It represents a novel approach to the question of how to be attentive to the problem of value in Australian culture, building on recent research by Meyrick, Phiddian and Barnett and complementing contemporary work on Australian book industry economics by Zwar, Throsby and others at Macquarie University. The results of this experiment indicate that integrated reporting, and in particular the  framework—an established, rigorous and internationally recognised form of reporting—can be effectively applied to a single local book title, drawing exclusively on publicly available data in a manner that effectively and efficiently articulates types of value that exceed the economic. While the  framework has its limitations, my overarching conclusion is that this form of value reporting has strong potential to contribute to timely and effective local book industry advocacy into the future.